CRIMINAL EVIDENCE THROUGH DNA FINGERPRINTING AND ITS IMPACT ON THE RIGHT TO PRIVACY - Laskri Ahcene (International Journal of Innovative Technologies in Social Science, 2025)
DNA fingerprinting has become one of the most significant pieces of evidence in criminal law today, prompting many countries to adopt it as a solution to various criminal cases. However, the rigid application of this technology may lead to significant difficulties, particularly concerning protecting individuals from potential violations of their right to privacy. Consequently, criminal legislation has worked to establish a set of guarantees that can effectively safeguard the right to privacy, as exemplified by the Algerian legislature.